2019
DOI: 10.1016/j.bbmt.2018.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Rates and Risk Factors for Post-Traumatic Stress Disorder Symptomatology among Adult Hematopoietic Cell Transplant Recipients and Their Informal Caregivers

Abstract: Hematopoietic cell transplant (HCT) can cause significant distress in patients and their informal caregivers. Despite advances in reduced-intensity conditioning and supportive care, few recent studies have reported rates of clinically significant post-traumatic stress disorder (PTSD) symptomatology. Goals of the current study were to examine rates of PTSD and distress in patients and caregivers and to identify sociodemographic and clinical risk factors for PTSD. As part of an annual survivorship survey, 2157 H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 30 publications
2
24
0
5
Order By: Relevance
“…FC of patients with mixed cancer diagnoses reported a decrease in unmet needs from 6 to 24 months post-diagnosis [ 41 ]. Our result reveals that many support needs do not diminish by themselves, which is in line with earlier studies showing that FC of allo-HSCT patients experience high levels of distress for a long time [ 10 , 11 , 15 ], which is related to the uncertainty of the situation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…FC of patients with mixed cancer diagnoses reported a decrease in unmet needs from 6 to 24 months post-diagnosis [ 41 ]. Our result reveals that many support needs do not diminish by themselves, which is in line with earlier studies showing that FC of allo-HSCT patients experience high levels of distress for a long time [ 10 , 11 , 15 ], which is related to the uncertainty of the situation.…”
Section: Discussionsupporting
confidence: 91%
“…FC often show high levels of distress, sometimes even higher than the recipients [4]. Until now, research on FC of HSCT recipients has mainly focused on their experiences [6][7][8], quality of life [6], psychological distress [7,[9][10][11] and caregiver burden [7,12].…”
Section: Introductionmentioning
confidence: 99%
“…Many disease-related factors have been found to enhance PTSD symptoms. The uncertainty related to disease and the family strain have been related to PTSD symptoms in a study on 333 caregivers of hematopoietic cell transplant recipients [52]. Richardson et al [53] found that in 78 caregivers of patients with head and neck cancer, having perceptions of low benefits from treatment and the presence of many patient symptoms, increased the risk of experiencing symptoms of PTSD in caregivers.…”
Section: Risk Factors For Ptsdmentioning
confidence: 99%
“…Furthermore, Dew et al [47] examined 190 family caregivers to heart transplant recipients and found that in the first year post-transplant, caregivers presented higher PTSD symptoms. A more recent study on informal caregivers of adult hematopoietic cell transplant recipients showed that a shorter time since transplant was associated with greater PTSD symptoms in caregivers [52]. Moreover, Teixeira and Pereira [54] found that a shorter disease and caregiving duration were associated with a poorer outcome in terms of PTSD symptomatology, while Carek et al [48], examining 51 caregivers of recent stroke survivors, found that an increased time since the event, with consequently more chronic stressors related to the sequelae of the medical event, was related to higher PTSD symptoms.…”
Section: Risk Factors For Ptsdmentioning
confidence: 99%
See 1 more Smart Citation